Electrospun Na3V2(PO4)3/C nanofibers as self-standing cathode material for high performance sodium ion batteries - Longlong Luo; Bin Cheng; Yuxin Chen; Shaojun Chen; Guanlun Liu; Haitao Zhuo (Materials Research Express, 2020)
This work focuses on the preparation of a 3D flexible Na _3 V _2 (PO _4 ) _3 /C fiber membrane, as self-standing cathode for Na-ion batteries, via a facile and simple electrospinning method, is followed by a hot-pressing process. A series of heat treatment temperatures are studied in detail, it is found that the temperature of the thermal process is a key parameter for controlling the structural organization of the material, as well as the size and dispersion of Na _3 V _2 (PO _4 ) _3 nanoparticles on the carbon surface. Hence, Na _3 V _2 (PO _4 ) _3 nanoparticles, with a size of 40 nm and highly disperse on the carbon nanofibers, are obtained after calcination at 800 °C. In addition, this sample (Na _3 V _2 (PO _4 ) _3 /C Nanofiber-800) exhibits the best electrochemical performances among all the samples. For instance, it displays a considerably high initial discharge capacity of 109, 84, 77, and 71 mA h g ^−1 at a current density of 0.1, 10, 20, and 30 C, respectively. Moreover, the Na _3 V _2 (PO _4 ) _3 /C Nanofiber-800 shows notable cycle stability with about 95.3% capacity retention of its initial capacity after 1000 cycles at 2 C, These high performances is attributed to the unique nanofiber structure and uniform distribution of Na _3 V _2 (PO _4 ) _3 nanoparticles in the highly conductive carbon matrix.